2014
DOI: 10.1074/jbc.m114.566448
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Myelin Transcription Factor 1 (MyT1) as a Subunit of the Neural Cell Type-specific Lysine-specific Demethylase 1 (LSD1) Complex

Abstract: Background:The composition of tissue-specific complexes that modify histone is largely unknown. Results: We identified myelin transcription factor 1 (MyT1) as a lysine-specific demethylase 1 (LSD1) complex component by biochemical approaches using Neuro2a cells. This complex directly regulated the phosphatase and tensin homolog (Pten) gene expression. Conclusion: MyT1 is a neuro-specific LSD1 complex component. Significance: A tissue-specific complex component of LSD1 complex was identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 65 publications
2
44
0
Order By: Relevance
“…Previous work in Neuro2a neuroblastoma cells with knock-down of Myt1 identified a list of genes that were altered on reduction of endogenous Myt1 expression. 18 Comparison of our data to this data-set revealed a relatively small overlap, although this is perhaps not surprising, given the different cell types and different analysis platforms (expression array versus RNA-seq). However, within the overlap between our Myt1 data and that from the knock-down the majority of genes had reduced expression in our Myt1 expressing cells and increased expression in the Myt1 knockdown analysis ( Figure 6A).…”
Section: Myt1l Expressing Cellsmentioning
confidence: 69%
“…Previous work in Neuro2a neuroblastoma cells with knock-down of Myt1 identified a list of genes that were altered on reduction of endogenous Myt1 expression. 18 Comparison of our data to this data-set revealed a relatively small overlap, although this is perhaps not surprising, given the different cell types and different analysis platforms (expression array versus RNA-seq). However, within the overlap between our Myt1 data and that from the knock-down the majority of genes had reduced expression in our Myt1 expressing cells and increased expression in the Myt1 knockdown analysis ( Figure 6A).…”
Section: Myt1l Expressing Cellsmentioning
confidence: 69%
“…All three genes are predominantly expressed in developing mammalian neural tissues 25. MYT1 is part of the lysine-specific demethylase 1 complex that plays a crucial role in the neural cell-specific regulation of gene expression 26. In Xenopus laevis , Myt1 was involved in primary selection of neuronal precursor cells, acting synergistically with neurogenin-1 in the Notch signalling pathway and allowing cells to escape lateral inhibition 27 28.…”
Section: Discussionmentioning
confidence: 99%
“…Then, they confirmed that the LSD1 complex directly bound to the PTEN (phosphatase and tensin homolog) gene promoter through MyT1 protein and demethylated H3K4me2 at its promoter. The Neuro2a‐cell proliferation was then decreased, due to downregulation of either Myt1 or LSD1 expression …”
Section: Biochemistry Of Lsd1mentioning
confidence: 99%
“…The Neuro2a-cell proliferation was then decreased, due to downregulation of either Myt1 or LSD1 expression. 64 Epithelial-mesenchymal transition (EMT) has been demonstrated to play pivotal roles during embryonic development and carcinoma progression. Lin et al showed that LSD1 was essential for Snail1-mediated transcriptional repression and for maintenance of the silenced state of Snail target genes in invasive cancer cells.…”
Section: Nonhistone Substrates Of Lsd1 and Protein-protein Interacmentioning
confidence: 99%